Prevalence of iodine deficiency disorders among school student of Purba Medinipur, 2018: a cross sectional study - Biswas, Dilip Kumar; Bhunia, Rama; Mukherjee, Abhijit (International Journal Of Community Medicine And Public Health, 2019)
Background: Iodine deficiency disorder is one of the preventable public health diseases in India. Prevalence of goiter is also still prevalence at sub-Himalayan region of West Bengal. Study was conducted to assess prevalence of goiter among school students between 6 and 12 years age, to find out urinary excretion of iodine and iodine content in salt sample and to recommend for consuming iodized salt. Methods: We conducted the study among the school students aged 6 to 12 years during the month of June 2018 in Purba Medinipur district, West Bengal, India. Multistage cluster sampling method was conducted for selecting the study population. Clinical examination was done by medical officer to detect goiters. Salt and urine samples were taken from the selected students and were sent to State Iodine Monitoring Laboratory, Kolkata for examination of iodine content in household salt samples and urine samples. Results: Total 2821 students were examined for survey. Over all prevalence of goiter was 3.75% (109/2821). Girls had more prevalence 4.63% than boys 3.18%. Average urinary iodine excretion (UIE) level is 184.74% in 30 clusters of 339 urine samples. Only 5.60% showed UIE level ≤100 microgram/liter. Total 541 household salt samples were tested for iodine and average iodine content was 22.85%. Among them 91.5% (495) had iodine ≥15 ppm indicating adequate iodine contents in salt samples. Conclusions:Purba Medinipur may be considered a non-endemic district. We recommended continuing use of iodized salt.